The Disappearing Openness-Inflation Relationship : A Cross-Country Analysis of Inflation Rates - Bleaney, M. (IMF Working Papers; Working Paper, 1999)
The robust negative correlation between openness and inflation found in cross-country data for the 1970s and 1980s has disappeared in the 1990s. There is now a strong negative correlation of inflation with per capita GDP, as higher-income countries have achieved significant disinflation not emulated by lower-income countries. Since 1973, the most consistent finding is that floating exchange rate regimes are associated with inflation rates at least 10 percent a year higher than pegged exchange rate regimes, after allowing for other factors. There is also a consistent positive correlation between land area and inflation.